Unerupted Lower Third Molar Extractions and Their Risks for Mandibular Fracture - Simoes Correa, Ana Paula [UNESP]; Faverani, Leonardo Perez [UNESP]; Ramalho-Ferreira, Gabriel [UNESP]; Ferreira, Sabrina [UNESP]; Souza, Francisley Ávila [UNESP]; Puttini, Igor de Oliveira [UNESP]; Garcia-Junior, Idelmo Rangel [UNESP] (Lippincott Williams & Wilkins, 2014)
As every surgical procedure extraction of third molars can result in several complications, among them the mandibular angle fracture. Predisposing factors for fracture should be analyzed during and after the surgery. This paper aims to discuss the predisposing factors to the occurrence of mandibular angle fractures during and after the procedure for third molars extraction, as well as surgical principles to avoid this complication.
Keywords: Impacted tooth; lower third molar; mandibular fracture